ANALISIS PENGARUH KEPUASAN KONSUMEN, KEPERCAYAAN, KOMITMEN DAN PERCEIVED VALUE PADA LOYALITAS KONSUMEN TERHADAP PENYEDIA JASA TRANSPORTASI (Studi pada pelanggan Rosalia Indah di Palur, Karanganyar) - Suratman, Andriyastuti (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
This study aims to determine the effect of consumer satisfaction, trust, commitment and perceived value on customer loyalty. Number of respondents in this study is users of transport services 239 customers in Palur Rosalia Indah. The results in this study are positive and significant effect of satisfaction on commitment, consumer confidence positive and significant effect on consumer commitment, satisfaction has a positive and significant impact on consumer confidence, perceived value and a significant positive effect on satisfaction, perceived value and a significant positive effect on consumer confidence, perceived value and a significant positive effect on consumer commitment, commitment consumers positive and significant effect on customer loyalty, customer satisfaction and a significant positive impact on customer loyalty, consumer confidence positive and significant effect on customer loyalty.